Body size and tree species composition determine variation in prey consumption in a forest-inhabiting generalist predator - Lantman Irene M.; Vesterinen Eero; Hertzog Lionel R.; Martel An; Verheyen Kris; Lens Luc; Bonte Dries (WILEY, 2022)
Trophic interactions may strongly depend on body size and environmental variation, but this prediction has been seldom tested in nature. Many spiders are generalist predators that use webs to intercept flying prey. The size and mesh of orb webs increases with spider size, allowing a more efficient predation on larger prey. We studied to this extent the orb-weaving spider Araneus diadematus inhabiting forest fragments differing in edge distance, tree diversity, and tree species. These environmental variables are known to correlate with insect composition, richness, and abundance. We anticipated these forest characteristics to be a principle driver of prey consumption. We additionally hypothesized them to impact spider size at maturity and expect shifts toward larger prey size distributions in larger individuals independently from the environmental context. We quantified spider diet by means of metabarcoding of nearly 1,000 A. diadematus from a total of 53 forest plots. This approach allowed a massive screening of consumption dynamics in nature, though at the cost of identifying the exact prey identity, as well as their abundance and putative intraspecific variation. Our study confirmed A. diadematus as a generalist predator, with more than 300 prey ZOTUs detected in total. At the individual level, we found large spiders to consume fewer different species, but adding larger species to their diet. Tree species composition affected both prey species richness and size in the spider's diet, although tree diversity per se had no influence on the consumed prey. Edges had an indirect effect on the spider diet as spiders closer to the forest edge were larger and therefore consumed larger prey. We conclude that both intraspecific size variation and tree species composition shape the consumed prey of this generalist predator.